TRP Channels and Small GTPases Interplay in the Main Hallmarks of Metastatic Cancer - Chinigò, Giorgia; Fiorio Pla, Alessandra; Gkika, Dimitra (Frontiers in Pharmacology, 2020)
Transient Receptor Potential (TRP) cations channels, as key regulator of intracellular calcium homeostasis, play a central role in all the essential hallmarks of cancer. Among the multiple pathways in which TRPs may be involved, in this review the ones involving small guanosine triphosphatases (GTPases) are summarized, focusing on the main processes associated with the metastatic cascade, such as migration, invasion and tumor vascularization. In the last decade several studies have highlighted a bidirectional interplay between TRPs and small GTPases in cancer progression, showing that TRP channels may affect small GTPases activity via both Ca2+-dependent or Ca2+–independent pathways, and, conversely, some small GTPases may affect TRP channels activity through the regulation of their intracellular trafficking to the plasma membrane or acting directly on channel gating. More specifically, we will describe the interplay showed by TRPC1, TRPC5, TRPC6, TRPM4, TRPM7 and TRPV4 with Rho-like GTPases in regulating cell migration, the cooperation of TRPM2 and TRPV2 with Rho GTPases in increasing cell invasiveness and finally, the crosstalk between TRPC1, TRPC6, TRPM8, TRPV4 and both Rho- and Ras-like GTPases in inducing aberrant tumor vascularization.